(untitled) (CIPEEX, 2026)
The 1988 Federal Constitution guarantees education as a right for all and a duty of the State and the family, and it should be promoted with the collaboration of society. However, its implementation, especially in the field of inclusive education, faces significant barriers in a context of constant social, economic, and technological changes, which Zygmunt Bauman calls “liquid modernity.” This study investigates how Public Administration can ensure the implementation of inclusive policies in a context of institutional instability and political volatility. Using a qualitative methodology and bibliographic research, the analysis considers normative documents such as the Federal Constitution, the Statute of the Person with Disabilities, and the National Education Plan, in addition to reference works by authors such as Bauman, Paulo Freire, Marcelo Neves, and Norberto Bobbio. The analysis indicates that inclusion goes beyond school infrastructure, which, although necessary, is not sufficient: inclusion also requires curriculum adaptation, teacher training, and participatory pedagogical practices. It is noted that the fragmentation of policies and the predominance of a technocratic logic reduce the transformative role of education. It is concluded that the implementation of inclusive education demands articulated governance, continuous funding, and an ethical commitment to human dignity, being, in liquid times, an essential pillar of democratic resilience and social justice.